2003
DOI: 10.1002/art.10706
|View full text |Cite
|
Sign up to set email alerts
|

Induction of matrix metalloproteinase 1 gene expression is regulated by inflammation‐responsive transcription factor SAF‐1 in osteoarthritis

Abstract: Objective. To identify specific transcription factors that are activated in the cartilage tissue of osteoarthritis (OA) patients and are involved in the expression of matrix metalloproteinase 1 (MMP-1).Methods. DNase I footprint and electrophoretic mobility shift assays were performed to identify active elements of the MMP1 promoter and the transcription factors that interact with it. The relative abundance of the involved transcription factor in the cartilage was determined by immunohistochemical analysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…MMP-1 activity was increased in the synovial fluid of OA joints in horses (Brama et al, 2004). Overexpression of serum amyloid A-activating factor 1 in OA chondrocytes increased the expression of the MMP-1 promoter; thus, serum amyloid A-activating factor 1 may be a therapeutic target for controlling the overexpression of MMP-1 in OA (Ray et al, 2003). Increased MMP-3 can induce matrix degradation of articular cartilage in mature bovines (Lin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-1 activity was increased in the synovial fluid of OA joints in horses (Brama et al, 2004). Overexpression of serum amyloid A-activating factor 1 in OA chondrocytes increased the expression of the MMP-1 promoter; thus, serum amyloid A-activating factor 1 may be a therapeutic target for controlling the overexpression of MMP-1 in OA (Ray et al, 2003). Increased MMP-3 can induce matrix degradation of articular cartilage in mature bovines (Lin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A region of the MMP-1 promoter (Ϫ153 to ϩ3) known to respond to mitogenic signaling was employed (30). 24 h after the transfection, cell cultures were either treated or not treated with the ligand collagen.…”
Section: Ddr2 Y740f Mutation Induces Mmp-1 Promoter Activity and Stimmentioning
confidence: 99%
“…A prominent characteristic of rheumatoid arthritis is an increase in the numbers of synovial fibroblasts, which produce proinflammatory cytokines and matrix metalloproteinases (MMPs) that erode bone and destroy cartilage (1,2). In recent studies, serum amyloid A-activating factor 1 (SAF-1) an inflammation-responsive transcription factor, was identified as a critical regulator of MMP-1 gene induction in chondrocytes and synovial fibroblast cells (3). SAF-1 belongs to a family of zinc finger proteins, and its human and mouse homologues are identified as MAZ (4) and Pur-1 (5), respectively.…”
Section: R Heumatoid Arthritis (Ra)mentioning
confidence: 99%
“…Although it is suggested that a modest increase in SAF-1 activity during chronic inflammation would increase the expression of its target genes (12), relatively little is known about the cellular consequences if this protein is significantly overproduced. Indeed, significant overexpression of SAF-1 has recently been seen in osteoarthritic cartilage tissue (3). To examine this, we overexpressed SAF-1 in the cells and monitored their fate.…”
Section: R Heumatoid Arthritis (Ra)mentioning
confidence: 99%